Reaction of Clients and Fitness Instructors to Noise in Fitness Centers - Zannin, Paulo Henrique Trombetta; Anjelo, Karyn Lia Hamad; Silveira, Andrei Rei Rodrigues (Issues and Development in Health Research Vol. 1, 2021)
Noise is increasingly associated with leisure activities in Brazil, including working out in fitness centers, where thousands of instructors and clients are exposed to high sound pressure levels for several hours a day without using any type of protection. This is a cause of concern for their mental and physical health. This research involved an evaluation of noise levels in fitness centers based on measurements of sound pressure levels – equivalent sound levels (Leq), minimum (Lmin) and maximum (Lmax) levels, simulations of acoustic parameters (reverberation time – RT and speech transmission index – STI), and identification of the effects of noise on instructors and clients. Data were collected during workout sessions using a Brüel & Kjær 2238 sound level meter. Computer simulations were performed using Odeon Room Acoustics v. 9.2 Combined software. The effects of noise on instructors and clients at fitness centers were identified based on their answers to a questionnaire. The data were analyzed statistically using R version 2.11.1 software, and the level of significance was set at 5% (p \(\le\) 0.05). The findings indicated that sound pressure levels (Leq) varied from 82 to 100 dB(A), reaching a maximum level (Lmax) of 117.2 dB(A), which exceeds the legally established noise level limits. Modifications made in fitness centers were found to reduce reverberation time and change the classification of the speech transmission index from poor to satisfactory, thereby improving the acoustic properties in these fitness centers. The effects most commonly reported by clients and instructors were tiredness and vocal fatigue. Fitness instructors reportedly underwent several vocal changes by the end of their workday, the most common one being hoarseness. It was concluded that, contrary to expectations, the environments of fitness centers where people seek to improve their health and engage in leisure activities present high sound pressure levels similar to those of industrial environments, causing extreme concern regarding the health of their clients and especially that of their working fitness instructors. The findings of this study clearly indicate the need for measures to minimize and control the harmful effects of noise in fitness centers. This can be achieved by controlling the exposure of fitness instructors and clients through noise reduction measures, such as the installation of noise absorption materials on the ceilings and walls of fitness centers. Another way to control noise is to reduce the sound levels of music played during workout sessions.